(untitled) (Research, Society and Development, 2020)
Mesosphaerum suaveolens (L.) is a species with high aromatic and therapeutic potential, widespread in the Northeast of Brazil. However, the conditions of the northeastern semiarid and the high content of salts contained in the soil and water used for irrigation may compromise plant development. Thus, the objective of this study was to evaluate the effect of salicylic acid as a saline stress attenuator on biomass accumulation and chlorophyll indices in M. suaveolens plants. The experiment was conducted in a protected environment belonging to the Center for Agricultural Sciences, Federal University of Paraíba, Areia-PB. The statistical design adopted was randomized blocks in incomplete 5 x 5 factorial scheme, with five electrical conductivities of irrigation water (ECw: 0.5; 1.45; 5.0; 8.55 and 10.0 dS m-1) and five doses of salicylic acid (0.0, 0.29, 1.0, 1.71 and 2.0 mM L-1) with four replications and two plants per plot, generated from the experimental Box Central Compound matrix. Dry matter accumulation of root, stem, leaves, shoot and total and chlorophyll indices ‘a’, ‘b’, total and chlorophyll a/b ratio were evaluated. Salinity caused serious damage, considerably reducing biomass accumulation and chlorophyll leaf indices of M. suaveolens plants. Salicylic acid did not mitigate the damage caused by salt stress.